organizational health, organizational commitment - عطية, طارق طعمة; مهدي, امنة عبد الكريم (Journal of Economics and Administrative Sciences, 2016)
AbstractDue to increased interest on organizations and the human element, organizational and environmental aspects of the organization Has been analyzed, and behavioral aspects of the members and what is the impact of each on the other, To give the recipe interaction between the organization and its environment, in order to bring about change in behavior appeared the concept of organizational health as a concept in a modern organizations, Either the organization to be stimulating good, healthy, and then called healthy organization Or that the situation be frustrating it is not good and unhealthy, so the cause of tension and anxiety, unhealthy organization is here The research aim to determine the existence of organizational health in AL-MA'MON University College and their impact on organizational commitment to faculty members,to achieve this goal the researcher from the theoretical literature and related studies conclude to the construction of the scheme shows the hypothetical relationship between the variables, the research adopted on studying the organizational health as an independent variable (Communication, Participation, Commitment, Morale, Corporate Reputation, Ethics, Performance Recognition, Goal Alignment, Leadership, Development, and Resource Utilization) as well as three variables representing the dependent variable adopted for organizational commitment of the faculty members in Al -MA'MON University College are:(emotional commitment, normative commitment, continuous commitment). The sample consisted of (90) faculty members in Al -MA'MON University College. The research found that the perception of faculty members the availability of the dimensions of organizational health came medium, and that the existence of such dimensions is reflected in the significant impact in the organizational commitment of the faculty members in the Al -MA'MON University College